TINGKAT KESEHATAN BANK BUMN SYARIAH DENGAN BANK BUMN KONVENSIONAL: METODE RGEC (Risk Profile, Good Corporate Governance, Earning dan Capital) - Nur Fitriana; Ahmad Rosyid; Agus Fakhrina (Fakultas Ekonomi Universitas Pekalongan, 2016)
This study aims to compare the level of health of sharia state-owned banks to conventional stateownedbanks using the latest instruments of Bank Indonesia, RGEC. Variables are compared namelyrisk profile, good corporate governance, earnings, and capital. Data are tested using Mann-Whitneyand the results show no significant difference between the two except on earnings. This difference isdue to the difference between the assets and the age of the two.Kata Kunci: RGEC, Bank BUMN Syariah, Bank BUMN Konvensional, Tingkat Kesehatan Bank